Evaluation of ISIS's Threats in the Middle East and Africa. Issue 1 (2nd January 2022) - Styszyński, Marcin
ABSTRACT: This article analyzes strategies of t he Islamic State in Iraq and Syria (ISIS) and its operational capacities in the Middle East and Africa. Jihadists have witnessed the collapse of the so-called caliphate, established by Abu Bakr al-Baghdadi in 2014. They have also suffered from shortage of supplies thanks to opposition forces that besieged insurgents in refugee camps, or isolated them in desert, mountainous, or rural territories. This research argues that the main objective of ISIS as an organization concerns implementation of local branches called Wilayat (provinces). The analysis of ISIS's activities highlights different measures launched by the group to achieve this approach. This article also demonstrates that jihadists managed to establish the Wilayat concept only in certain countries, and in regions such as the Sahel, and that they faced obstacles in other parts of the Middle East and Africa that have been dominated by Al-Qaeda's activities.